P471 Lymphogranuloma venerum in Quebec, Canada: five years of epidemiological survey, 2013–2017. (14th July 2019) - Diallo, Dieynaba; Venne, Sylvie; Labb, Annie-Claude; Fiset, Marc; Markowski, France; Murphy, Donald; Longtin, Jean; Dionne, Marc; Boutin, Catherine-Audrey; Blouin, Karine
Abstract : Background: Reported cases of lymphogranuloma venerum (LGV) were unusual in Quebec before 2005, when a first epidemic occurred (25 cases in 2005, 44 cases in 2006). This was followed by a low-endemicity period between 2007 and 2012 (2 to 13 cases/year). Since 2013, the number of reported LGV cases strongly increased with a peak in 2016 (2013: 49, 2014: 61, 2015: 105, 2016: 124 and 2017: 105). We hereby report on enhanced LGV surveillance between January 1st 2013 and December 31st 2017. Methods: We used data from the notifiable diseases records, epidemiological investigation questionnaires and genotyping to describe the evolution of this resurgence. Since June 2016, all Chlamydia-positive anorectal samples are sent to the Laboratoire de santé publique du Québec for genotyping. Collected information includes demographics, risk factors (for the past year unless otherwise indicated), clinical manifestations, laboratory tests and treatments. Results: All male reported cases (442, 97% confirmed) were analyzed (399 with available questionnaire). Most cases were L2b genotype (98%) and lived in Montreal (81%). Mean age was 40 years. Almost all (97%) were men who have sex with men (MSM), 94% reported past sexually transmitted infection (STI) and 78% were HIV-infected (243/311). LGV-specific symptoms were reported by 69% of cases, 11% mentioned non LGV-specific symptoms and 21% were asymptomatic. Sex partners outside Quebec were reported by 37% of cases, 51% have had more than 10 sex partners and 58% have used recreational drug. LGV reinfection occurred among 45 persons (11%): 36 had 2 episodes, 9 had 3 episodes and 1 had 4 episodes. In 2017 (first complete year of routine genotyping on Chlamydia-positive anorectal samples), 100/1591 (6.3%) were LGV genotypes. Conclusion: The LGV epidemic is still ongoing. Cases are mostly from urban regions, are almost exclusively MSM and frequently report past STIs, a high number of sex partners and drugs use. Disclosure: No significant relationships.